2021
DOI: 10.1002/lt.25974
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Outcomes in Older Patients With Hepatocellular Carcinoma Are Driven by Non–Hepatocellular Carcinoma Factors

Abstract: The incidence of hepatocellular carcinoma (HCC) is growing in the United States, especially among the elderly. Older patients are increasingly receiving transplants as a result of HCC, but the impact of advancing age on long-term posttransplant outcomes is not clear. To study this, we used data from the US Multicenter HCC Transplant Consortium of 4980 patients. We divided the patients into 4 groups by age at transplantation: 18 to 64 years (n = 4001), 65 to 69 years (n = 683), 70 to 74 years (n = 252), and ≥75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Imaging technology continues to evolve to address the current gaps, and corresponding evolution in pathologic analysis may be warranted. Emerging evidence supports that scoring systems integrating imaging-based tumor characteristics and clinical variables are most predictive of prognosis and achieve better patient selection and risk stratification [36,48,52]. Further, incorporation of molecular data may help to inform biologic aggressiveness and individual risk of post-transplant recurrence and/or need for adjuvant therapies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging technology continues to evolve to address the current gaps, and corresponding evolution in pathologic analysis may be warranted. Emerging evidence supports that scoring systems integrating imaging-based tumor characteristics and clinical variables are most predictive of prognosis and achieve better patient selection and risk stratification [36,48,52]. Further, incorporation of molecular data may help to inform biologic aggressiveness and individual risk of post-transplant recurrence and/or need for adjuvant therapies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ongoing research suggests that other imaging features may be important prognostic markers for recurrence and tumor aggressiveness, such as LR-M features [47]. Likewise, as the understanding of molecular alterations in HCC advances, it may be useful to revisit the utility of biopsy for prognostication even if the diagnosis of HCC is not in question, or to consider the combination of imaging and pathomolecular and clinical variables, rather than tumor size and number alone as in current management [36,48].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ciccarelli et al [24] reported no difference in RFS between patients with 1-2 or > 2 bridging LRTs (p = 0.24). Similarly, Adeniji et al [18] found RFS did not differ between patients who received 1-3 LRTs when compared to no LRT; however, patients who received 4 LRTs had worse RFS than patients without LRT (HR: 1.4, 95% CI: 1.1-1.8), although there was no difference in OS by number of LRTs. Agopian et al [19] reported an increased risk of recurrence with 3+ TACE (HR: 2.58, p = 0.001) or 3+ ablation (HR: 2.58, p < 0.001), compared to 1 session.…”
Section: Number Of Treatmentsmentioning
confidence: 84%
“…HCC remains the leading indication for LTs in the United States, with an increasing proportion of elderly patients receiving transplants. 13,14 Even as age cut-off levels fall out of favor for patients who can receive an LT across high-volume centers, concerns remain over the impact of older age on clinical outcomes. 15,16 In this study investigating survival outcomes among elderly patients with HCC, we found that most patients underwent HR.…”
Section: Resultsmentioning
confidence: 99%